1991
DOI: 10.1063/1.105296
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in sidewall recombination velocity by selective disordering in GaAs/AlGaAs quantum well mesa structures

Abstract: Sidewall recombination in SiO2-capped GaAs/AlGaAs multiple quantum well mesa structures is investigated using a time-resolved photoluminescence technique. Nonradiative recombination lifetimes in annealed samples are improved significantly compared with those in samples which are not annealed. This effect contributes to a reduction in sidewall recombination velocity due to disordering of quantum wells at the sidewall by cap annealing. Numerical analysis is used to fit the experimentally observed sample size dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…PL intensity rapidly decreased with decreases in stripe width for as-etched wafers, which is the same as findings previously reported. 6 However, ex situ regrowth using solidsource MBE with H 2 SO 4 treatment, allowed the slope to decrease. This means that surface recombination was depressed by epipassivation.…”
Section: B Epitaxial Passivation Of Gaas/algaas Stripesmentioning
confidence: 99%
See 2 more Smart Citations
“…PL intensity rapidly decreased with decreases in stripe width for as-etched wafers, which is the same as findings previously reported. 6 However, ex situ regrowth using solidsource MBE with H 2 SO 4 treatment, allowed the slope to decrease. This means that surface recombination was depressed by epipassivation.…”
Section: B Epitaxial Passivation Of Gaas/algaas Stripesmentioning
confidence: 99%
“…The lifetime of excited carrier was measured for different stripe widths. In this stripe structure, is connected to stripe width w as follows: 6 1/ϭ1/ b ϩ2S v /w. b : nonradiative lifetime of the unpatterned sample.…”
Section: B Epitaxial Passivation Of Gaas/algaas Stripesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because a reduction of carrier lifetime due to surface recombination or large optical losses in the cavity due to insufficient cavity structure raises the threshold current density. Although a quantitative characterization of surface recombination by time-resolved photoluminescence has been done, 6 no direct observation of the optical losses in a microcavity has been reported. When the cavity diameter is reduced to a few m, it is supposed that the optical loss is dominated by scattering losses on the cavity sidewall with process-induced microroughness.…”
Section: Introductionmentioning
confidence: 99%
“…In these fine structures, however, when the surface of the fabricated active region is exposed to air, the resulting surface states easily cause carrier loss even if process-induced damage is completely removed. Hamao et al 8 found that when using flat AlGaAs/GaAs interfaces, in situ sample manipulation in an UHV environment restrained increase in nonradiative carrier recombination velocity, S, which severely occurred in the ex situ process. [1][2][3] In this context, in situ processing, where dry etching and crystal overgrowth are successively performed under ultrahigh vacuum ͑UHV͒ condition, is expected to provide processed/regrown interfaces with excellent quality owing to avoiding air-related contamination.…”
Section: Introductionmentioning
confidence: 99%